Pengaruh Corporate Governance terhadap Kinerja Keuangan dan Kebijakan Dividen - Yuni, Yuni Mahmuda; Agnes, Agnestiyan Putri Ilmawati (Journal of Economic, Management and Entrepreneurship, 2024)
The purpose of this study was to determine the effect of corporate governance on financial performance and dividend policy in banking sector companies listed on the Indonesia Stock Exchange in 2014-2018. The study population was 43 banking companies. The sampling technique used was purposive sampling and obtained a research sample of 9 banking companies. The data analysis technique used is Partial Least Square (PLS). The independent variable used is corporate governance. as measured by the audit committee, institutional ownership and by the independent commissioner. The dependent variables used are financial performance and dividend policy. Financial performance is measured by return on assets (ROA) and return on equity (ROE). Meanwhile, dividend policy is measured by dividend payout ratio (DPR), dividend yield (DY) and dividend per share (DPS). The results showed that corporate governance directly affected financial performance; Directly, corporate governance does not affect dividend policy; and financial performance directly affects dividend policy